Born to run - Morpurgo, Michael 1943-; Foreman, Michael Illustrator (London : Harper Collins, 2007)
Joy and heartbreak combine in this bittersweet tale of a champion greyhound's journey through life - and from owner to owner... "The sack wasn't just drifting gently along like everything else, it was turning of its own accord. There was definitely something inside it, struggling against the side of the plastic bag, kicking at it, squeaking and squealing in terror. He had no idea what it might be, only that it was alive and in danger of drowning." When Patrick saves a litter of greyhound puppies from the canal, he can't bear to hand them all over to the RSPCA. He pleads with his parents: couldn't he just keep one of them? But nothing will convince them and Patrick cries himself to sleep - only to be woken by a greyhound puppy licking his face! Patrick christens his puppy Best Mate, and that's what he becomes. Patrick's favourite thing is to watch Best Mate running at full stretch on the heath, a speeding bullet, a cheetah-dog. Until one day Best Mate is kidnapped by a greyhound trainer, and begins a new life as a champion race dog. Suzie, the greyhound trainer's step-daughter, loves Best Mate on first sight and gives him a new name, Bright Eyes. But what will happen when he can't run any more?
Keywords: Greyhound -- Dogs - Fiction; Young adult